2020
DOI: 10.1080/17453674.2020.1836322
|View full text |Cite
|
Sign up to set email alerts
|

Are functional outcomes and early pain affected by discharge on the day of surgery following total hip and knee arthroplasty?

Abstract: Gromov (2020): Are functional outcomes and early pain affected by discharge on the day of surgery following total hip and knee arthroplasty?, Acta Orthopaedica,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
3
12
1
Order By: Relevance
“…Our findings were also in accordance with Husted et al (2021), who found a median OKS 3 months postoperatively of 32 and 31 in the group discharged on day of surgery and not discharged on day of surgery, respectively. We found in our analysis of fast-track TKA patients a median OKS at 3 months of 35 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were also in accordance with Husted et al (2021), who found a median OKS 3 months postoperatively of 32 and 31 in the group discharged on day of surgery and not discharged on day of surgery, respectively. We found in our analysis of fast-track TKA patients a median OKS at 3 months of 35 .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies on early function, pain, and quality of life outcomes after TKA have been published (Andersen et al 2009, Larsen et al 2012, Jakobsen et al 2014, Castorina et al 2017, Schotanus et al 2017, Husted et al 2021. Moreover, Canfield et al (2020) concluded that most improvement in function and pain is gained during the first 6 months postoperatively.…”
mentioning
confidence: 99%
“…The cohort of patients included in this study is the same as in a previously published study (Husted et al 2021). That study investigated whether patient-reported outcomes were affected by DDOS after THA and TKA.…”
Section: Methodsmentioning
confidence: 99%
“…That study investigated whether patient-reported outcomes were affected by DDOS after THA and TKA. Patients with an ASA score of 1-2 without sleep apnea requiring treatment, undergoing primary unilateral THA or TKA as 1st or 2nd in the surgical theater between January 2016 and June 2017 were scheduled for same-day discharge as previously described (Gromov et al 2017, Husted et al 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation